The Efficacy of Backward Walking on Static Stability, Proprioception, Pain, and Physical Function of Patients with Knee Osteoarthritis: A Randomized Controlled Trial. (11th June 2021) - Chen, Zehua; Ye, Xiangling; Wang, Yi; Shen, Zhen; Wu, Jiatao; Chen, Weijian; Jiang, Tao; Wu, Huai; Xu, Xuemeng
Abstract : Objective . Impaired static stability and proprioception have been observed in individuals with knee osteoarthritis (KOA), which serves as a major factor increasing risk of fall. This study aimed to investigate the effects of backward walking (BW) on static stability, proprioception, pain, and physical function in KOA patients. Methods . Thirty-two subjects with knee osteoarthritis were randomly assigned to either an BW group (BG, n  = 16) or a control group (CG, n  = 16). The participants in the BG received combination treatment of a 4-week BW training and conventional treatments, while those in the CG was treated with conventional treatments alone. All the participants were tested for the assessment of static stability [center of pressure (COP) sway, including sway length (SL, mm) and sway area (SA, mm 2 )] and proprioception [average trajectory error (ATE, %) and completion time (CT, second)]. Additionally, pain and knee function scores were measured by the numerical rating scale (NRS) and the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index, respectively. The assessments were conducted before and after intervention. Results . The COP sway (SA and SL), ATE, NRS, and WOMAC showed a significant decline at week 4 in the two groups in contrast to their baseline (P < 0.05 ). Moreover, after 4-week intervention, the SA [(610.50 ± 464.26) mm 2 vs. (538.69 ± 420.52) mm 2 ], NRS [(1.56 ± 0.63) vs. (2.25 ± 0.86)], and WOMAC [(11.69 ± 2.50) vs. (16.19 ± 3.94)] showed a significantly greater decrease in the BG compared to the CG (P < 0.05, respectively). However, the proprioception (ATE and CT) was closely similar between both groups at week 4 (P > 0.05 ). Conclusion . BW is an effective adjunct to conventional treatment in reducing pain, improving physical function and static stability for KOA patients. It should be taken into consideration when developing rehabilitation programs for people with KOA.